The Impact of School Inspection on Teaching and Learning in a Private School in Ras Al Khaimah - NOFAL, DOAA ABDULRAHIM (2023)
This study reveals impact of school inspections teaching and learning in RAK. School inspections are one of the hardest things about teaching; It stands for an accountability-based approach to teaching and learning. Moreover, Decision-makers in policy-making receive precise information on the current condition of education in their particular institutions via school inspections. The main aims of this study are to examine what extent School inspections are supporting teaching and learning in RAK private schools and to offer a few recommendations on how to carry out efficient school inspections that will enhance instruction. The methodology employed in this study is qualitative and quantitative approach. The primary research instruments used in this study include questionnaires, interviews, and documentaries. This study included 51 participants; school principal, 5 lead-teachers, 5 head of departments and 40 teachers, from private school who follow Ministry of Education of curricula conducted in the 2023/2024 academic year. The results demonstrate that school inspection plays a major part in improving schools, particularly in terms of teaching and learning, Instructors accept the feedback they receive from inspectors. However, Teaching and learning are negatively impacted by school inspections as well.; For example, school inspection compels certain schools to demonstrate activities they have never conducted before. Moreover, in certain instances, the recommendations and inspection reports for the school lack depth and are unrelated to the school context. However, there isn't a very good rapport between inspectors and teachers. This study makes several recommendations on how school inspections should be improved.